Asia Pacífico frente al Acuerdo de París contra el cambio climático: geopolítica y cooperación - Cuevas Tello, Ana Bertha; Preciado Caballero, Nora Elena (El Colegio de México, 2017)
Given the complexity surrounding climate change, it is argued that the willingness to cooperate on the part of the States is based on one of the faces that, for the climate field, can offer geopolitics: strengths or weaknesses (understood as vulnerability) of geographical conditions, location and territory. That is, the physical, geographic, economic and demographic factors of each State influence the decision making of the foreign climate policy, which induces them to cooperate or the abstention of it. This paper will address, broadly speaking, the participation of the main economies of the Asia-Pacific region in the institutionalization of climate change in the International Agenda; the importance of the economies of the Asia-Pacific region with regard to the Paris Agreement; and the geopolitical strengths and weaknesses that explain the cooperative or non-cooperative behavior of the region in the fight against climate change.